Using the information technology of virtual-reality in architectural activities - Khymytsia, Olha (Видавництво Львівської політехніки, 2017)
The main properties of the virtual reality are characterized. Prospects application technology of virtual reality: Fast 3D City Model Generation, VE CADWall, Building Design Suite and Creation Suite in architectural activity are analyzed.
Keywords: information technology; information system; virtual reality; architectural activity; аrchitectural desig; building structure